High-water-resistance polymer waterproof coating and preparation method thereof

By using a technology that combines acrylate emulsion with hybrid porous graphene microns, a dense interpenetrating network structure is formed, which solves the problems of existing waterproof coatings being prone to cracking, high water absorption and insufficient wear resistance under thick coating construction conditions, and achieves waterproof coatings with low water absorption, high wear resistance and stability.

CN120118570APending Publication Date: 2025-06-10SHANGHAI WEIXING NEW MATERIAL TECH CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510357786.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-25
Publication Date
2025-06-10

AI Technical Summary

Technical Problem

The existing high water-resistant polymer waterproof coatings are prone to cracking under thick coating construction conditions, have high water absorption, insufficient wear resistance, and poor stability in alkaline environments.

Method used

The technology of combining acrylate emulsion with hybrid porous graphene microns is adopted to form a dense interpenetrating network structure through cross-linking reaction, reducing water absorption, and improving the wear resistance of the coating film through non-permeable polymer hollow microspheres on the surface of polystyrene.

Benefits of technology

It significantly reduces the water absorption rate of the coating film, improves its water impermeability and wear resistance, avoids the problem of thick coating cracking, and maintains stability in an alkaline environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005327811040000171
    Figure BDA0005327811040000171
Patent Text Reader

Abstract

The invention relates to the field of waterproof coatings, in particular to a high-water-resistance polymer waterproof coating and a preparation method thereof. The preparation raw materials of the high-water-resistance polymer waterproof coating provided by the invention comprise a liquid material and a powder material, wherein the liquid material is prepared from the following raw materials in parts by mass: 80 to 90 parts of acrylate emulsion, 0.1 to 0.5 part of wetting agent, 0.1 to 0.3 part of coalescing agent, 0.1 to 0.3 part of defoaming agent and 5 to 30 parts of water; the powder material is prepared from the following components in parts by mass: 32 to 85 parts of filler, 0.1 to 0.6 part of water reducing agent, 2 to 4 parts of polystyrene surface non-permeable polymer hollow microspheres, 3 to 5 parts of hybrid porous graphene microflowers and 20 to 50 parts of cement. The prepared high-water-resistance polymer waterproof coating is excellent in water resistance, the water absorption rate is lower than 5%, the hardness of the coating is high, and the high-water-resistance polymer waterproof coating can be applied to internal corner stacking scenes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of waterproof coatings, and particularly to a highly water-resistant polymer waterproof coating and a preparation method thereof. Background Art

[0002] As a new type of high-performance building material, highly water-resistant polymer waterproof coatings are currently widely used in waterproof engineering fields such as buildings, tunnels, and bridges due to their excellent water resistance, durability, and anti-aging properties. However, there are still some technical defects in this type of coating in the prior art. Firstly, the coating film is prone to cracking under thick coating construction conditions, especially at the structural internal corner parts. Secondly, the wear resistance of the coating layer is insufficient, and waterproof failure is likely to occur due to mechanical wear after long-term use. Thirdly, compared with solvent-based coatings, its water absorption rate is relatively high, affecting the durability of the waterproof effect. Fourthly, some polymer components are prone to degradation in an alkaline environment, and the long-term durability of the product will be affected to a certain extent.

[0003] Chinese Patent Application CN115011156A discloses a highly water-resistant polymer cement waterproof coating. The coating includes a liquid material and a powder material. The liquid material includes 1-11% of water, 0.2-0.4% of defoamer, 88-98% of styrene-butadiene emulsion, 0.2-0.5% of preservative, and 0.1-0.4% of thickener by weight percentage; the powder material includes 60-80% of cement and 20-40% of quartz sand; although the styrene-butadiene emulsion-based polymer cement waterproof coating reduces the water absorption rate by optimizing the ratio of the liquid material to the powder material, it does not improve the problem of cracking in thick coatings, and the degradation risk of styrene-butadiene emulsion in an alkaline environment will still lead to a decline in anti-aging performance. Chinese Patent Application CN114854260A discloses a cement-based polymer waterproof coating, and its preparation raw materials include 50-80 parts of polyacrylate emulsion, 30-50 parts of basic mixture, 15-25 parts of fusion agent, 5-15 parts of organosilicon waterproof agent, 20-30 parts of quick-setting agent, 0.1-0.35 parts of expansion agent, 0.5-0.15 parts of bactericide, 0.05-0.1 parts of water reducer, and 0.8-0.25 parts of defoamer by mass; this prior art mainly improves the compatibility between the polymer and cement and the film-forming speed by adding a fusion agent and a quick-setting agent, but it still cannot effectively solve the construction problem of cracking of the coating film at the internal corner. Chinese Patent CN110591009B discloses a graphene oxide-enhanced waterproof polymer emulsion, and its preparation raw materials include an amide-based hydrophilic small monomer for emulsification, an alkyl-based hydrophobic small monomer for emulsification, emulsion initiator a, chain transfer agent, amide-based hydrophilic small monomer, flexible small monomer, ether-based polymer, initiator b, alkyl-based hydrophobic small monomer, acrylate-based hard monomer, crosslinking agent, neutralizer, pH regulator, functional monomer, and deionized water; this solution enhances the adhesion and wear resistance of the coating film by introducing graphene oxide and amide-based monomers, but the introduction of amide-based hydrophilic monomers leads to a significant increase in the water absorption rate of the coating film.

[0004] In summary, existing highly water-resistant polymer waterproof coatings still have technical problems such as high sensitivity to cracking when thickly coated, difficulty in balancing water absorption and durability, and insufficient stability in alkaline environments. Therefore, there is an urgent need to develop a new type of waterproof coating that has low water absorption, high strength, resistance to thick coating construction, and long-term stability. Summary of the invention

[0005] In order to solve the above technical problems, the first aspect of the present invention provides a highly water-resistant polymer waterproof coating, the raw materials for its preparation include liquid and powder; wherein the raw materials for the preparation of the liquid include, by weight, 80-90 parts of acrylic emulsion, 0.1-0.5 parts of wetting agent, 0.1-0.3 parts of film-forming aid, 0.1-0.3 parts of defoaming agent and 5-30 parts of water; the raw materials for the preparation of the powder include, by weight, 32-85 parts of filler, 0.1-0.6 parts of water reducer, 2-4 parts of polystyrene surface non-permeable polymer hollow microspheres, 3-5 parts of hybrid porous graphene microflowers, and 20-50 parts of cement.

[0006] As an implementable case, the mass ratio of the liquid material to the powder material is 1:1.5-2.5.

[0007] Liquid material

[0008] As an implementable example, the acrylic ester emulsion includes anionic acrylic ester emulsion.

[0009] Further, the brand of the acrylic emulsion is 8316A, purchased from Wanhua Chemical Group.

[0010] 8316A acrylic emulsion has excellent film-forming properties and chemical stability, and can efficiently combine with cement, hybrid porous graphene microflowers and other components in the powder to form a dense interpenetrating network structure, significantly improving the mechanical properties of the coating. The molecular chain structure of 8316A undergoes a cross-linking reaction with the nano-cuprous chloride loaded on the hybrid porous graphene micro-flowers, which enhances the compactness of the coating and can significantly reduce the water absorption rate of the waterproof coating, effectively solving the problem of water absorption and swelling of traditional polymer waterproof coatings and cracking of thick coatings. The synergistic effect of 8316A acrylic emulsion and the non-permeable hollow microspheres on the polystyrene surface further optimizes the lubricity and wear resistance of the coating to meet the construction requirements of complex base surfaces.

[0011] As an implementable case, the wetting agent includes one of AEO-9 (fatty alcohol polyoxyethylene ether), sodium dodecyl sulfate or sodium dodecylbenzene sulfonate.

[0012] Further, the wetting agent is AEO-9.

[0013] As an implementable case, the film-forming auxiliary is 1,2-propanediol.

[0014] 1,2-propanediol has a relatively low freezing point, which can significantly reduce the freezing risk of the waterproof coating, ensuring that the coating can still maintain fluidity during construction in a low-temperature environment, and avoiding performance deterioration or delamination problems caused by icing. At the same time, as a polar solvent, 1,2-propanediol can improve the compatibility between the acrylate emulsion in the liquid material and the cement and hybrid porous graphene microflowers in the powder material, promote the uniform dispersion of solid particles, reduce the agglomeration phenomenon, and thus improve the uniformity and construction smoothness of the waterproof coating.

[0015] As an implementable case, the defoamer includes mineral oil defoamers or silicone defoamers.

[0016] Further, the defoamer is a mineral oil defoamer.

[0017] Further, the mineral oil defoamer is NOPCO NXZ defoamer.

[0018] As an implementable case, the preparation method of the liquid material includes: mixing acrylate emulsion, wetting agent, film-forming auxiliary, defoamer and water evenly to obtain the liquid material.

[0019] Powder material

[0020] As an implementable case, the filler includes talc powder, heavy calcium powder and quartz sand.

[0021] Further, the mass ratio of the talc powder, heavy calcium powder and quartz sand is (2 - 10):(10 - 35):(20 - 40).

[0022] Further, the grade of the talc powder is LJ-110, purchased from Shanghai Liangjiang Chemical Products Co., Ltd.

[0023] Further, the heavy calcium powder is coating-grade heavy calcium powder, purchased from Shanghai Liangjiang Chemical Products Co., Ltd.

[0024] Further, the mesh number of the quartz sand is 80 - 120 mesh, purchased from Changxing Jinlan New Materials Technology Co., Ltd.

[0025] In the present invention, the filler is defined as a three-component compound of talcum powder, heavy calcium powder and quartz sand. This is mainly because the flaky filling of talcum powder, the micron-sized void filling of heavy calcium powder and the framework support of quartz sand work together to reduce the internal pore size of the waterproof coating, so that the water absorption rate is reduced to less than 5%. At the same time, the flexibility of talcum powder and the rigidity of quartz sand are complementary, avoiding the problem of low film hardness caused by a single filler. Therefore, the waterproof coating has a certain mechanical rigidity.

[0026] As an implementable case, the water reducer includes a polycarboxylate water reducer.

[0027] Furthermore, the polycarboxylate water reducer has the brand Sika 540P, which is an ordinary commercially available product.

[0028] As an implementable case, the cement includes P.O 42.5 cement.

[0029] Furthermore, the P.O 42.5 cement is P.O 42.5 Conch Cement.

[0030] As an implementable case, the polystyrene surface non-permeable polymer hollow microspheres have a particle size of 10 - 30 μm and are purchased from Beijing Zhongke Keyou Technology Co., Ltd.

[0031] Adding the polystyrene surface non-permeable polymer hollow microspheres to the waterproof coating of the present invention can control the density and thickness of the coating, optimize the viscosity of the waterproof coating, improve the brushing feel, and improve the lubricity and wear resistance of the waterproof coating.

[0032] As an implementable case, the preparation raw materials of the hybrid porous graphene microflowers include cuprous chloride, porous graphene microflowers and an alkaline solvent.

[0033] Furthermore, the alkaline solvent includes an aqueous potassium hydroxide solution.

[0034] Furthermore, the mass ratio of cuprous chloride to porous graphene microflowers is 1:(12 - 14).

[0035] Furthermore, the mass ratio of cuprous chloride to the alkaline solution is (1 - 3):100, that is, the mass concentration of cuprous chloride in the alkaline solution is 1 - 3 wt%.

[0036] As an implementable case, the preparation method of the hybrid porous graphene microflowers includes:

[0037] S1. Obtain graphene oxide microflowers by spray drying a monolayer graphene oxide suspension (purchased from Hangzhou Gaoxi Technology Co., Ltd., with a lateral size of 20 - 30 μm) at 140°C. The nozzle used for spray drying is in a two-fluid mode;

[0038] S2. Reduce graphene oxide microflowers using hydrazine, where the mass ratio of hydrazine to graphene oxide microflowers is 1:

[0039] (2 - 5). Mix the two and place them in an oven at 80 - 100 °C for 12 h. At this time, the mixture changes from yellow to black, and then calcine it in an N 2 environment at a calcination temperature of 1300 - 1500 °C to obtain porous graphene microflowers;

[0040] S3. Disperse cuprous chloride and porous graphene microflowers in an alkaline solvent, and react ultrasonically at 25 - 40 °C for 1 - 3 h. Then filter and collect the product and wash it to obtain a mixture;

[0041] S4. Calcine the mixture in an N 2 environment at a calcination temperature of 400 - 420 °C to obtain hybrid porous graphene microflowers.

[0042] In the present invention, the porous graphene microflowers have a flower-like structure and can load nano-cuprous oxide (cuprous chloride will turn into cuprous oxide after reaction and be loaded on the porous graphene microflowers) to obtain hybrid porous graphene microflowers. During the drying process of the coating film, the hybrid porous graphene microflowers can improve the integrity of the interpenetrating network structure of the waterproof coating, optimize the spatial distribution of the polymer molecular carbon chains. Therefore, the cross-linking reaction rate inside the coating is accelerated, and it can better resist the shrinkage during the drying process of the coating. Therefore, the product can be applied to the corner piling scenario and has the technical effect of no cracking when thickly coated.

[0043] As an implementable case, the preparation method of the powder includes: uniformly mixing a filler, a water reducer, polystyrene surface non-permeable polymer hollow microspheres, hybrid porous graphene microflowers and cement to obtain the powder.

[0044] Mix the powder and the liquid material evenly to obtain a high water-resistant polymer waterproof coating.

[0045] Beneficial effects

[0046] (1) After the use of polystyrene surface non-permeable polymer hollow microspheres in the present invention, the wear resistance of the waterproof coating film is significantly enhanced, ensuring that it is not damaged during the drying process, and making the coating film have high hardness and wear resistance.

[0047] (2) In the present invention, the flower-like structure of the porous graphene microflowers is prone to adsorbing acrylate latex and tiny cement particles, promoting the full progress of the cross-linking reaction, and improving the compatibility between the two at the same time. The cuprous oxide loaded on the porous graphene microflowers (cuprous chloride will turn into cuprous oxide after the reaction and be loaded on the porous graphene microflowers) undergoes a cross-linking reaction with the COO- on the acrylate molecular chain, increasing the active cross-linking sites in the system, improving the coating compactness, reducing the water absorption rate of the coating film to below 5%, greatly enhancing the water impermeability of the waterproof coating, and reducing the risk of water absorption swelling and waterproof failure.

[0048] (3) The flower-like structure of the porous graphene microflowers and the nano-cuprous oxide loaded thereon improve the integrity of the interpenetrating network structure during the drying process of the coating film, optimize the spatial distribution of the polymer molecular carbon chains, accelerate the cross-linking reaction inside the coating, can better resist the shrinkage during the drying process of the coating, achieve the effect of no cracking for thick coatings, and enhance the wear resistance of the coating film.

[0049] (4) The polystyrene surface non-permeable polymer hollow microspheres added in the present invention can control the density and thickness of the coating, optimize the viscosity of the coating material, improve the brushing feel, and enhance the lubricity of the coating material, making the construction more convenient and efficient.

[0050] (5) Through the scientific ratio of the raw material components of the liquid material and the powder material in the present invention, the waterproof coating achieves a good balance in performance indicators such as hardness, wear resistance, water absorption rate, tensile strength, and elongation at break, with excellent overall performance, and can meet the requirements of various waterproof projects for buildings, tunnels, bridges, etc. Specific Embodiments

[0051] Example 1

[0052] In the first aspect of this example, a highly water-resistant polymer waterproof coating is provided, and its preparation raw materials are a compound of a liquid material and a powder material; among them, the preparation raw materials of the liquid material are, by mass fraction, specifically 80 parts of acrylate emulsion, 0.1 part of wetting agent, 0.1 part of film-forming aid, 0.1 part of defoaming agent, and 19.7 parts of water; the preparation raw materials of the powder material are, by mass fraction, specifically 52 parts of filler, 0.1 part of water reducing agent, 2 parts of polystyrene surface non-permeable polymer hollow microspheres, 3 parts of hybrid porous graphene microflowers, and 44.9 parts of cement.

[0053] The mass ratio of the liquid material to the powder material is 1:1.5.

[0054] The brand of the acrylate emulsion is 8316A, purchased from Wanhua Chemical Group.

[0055] The wetting agent is AEO-9, and the model is A9N, purchased from BASF SE.

[0056] The film-forming auxiliary is 1,2-propanediol.

[0057] The defoamer is NOPCO NXZ defoamer.

[0058] The preparation method of the liquid material includes: mixing acrylate emulsion, wetting agent, film-forming auxiliary, defoamer and water evenly to obtain the liquid material.

[0059] The filler is a compound of talc powder, heavy calcium powder and quartz sand.

[0060] The mass ratio of the talc powder, heavy calcium powder and quartz sand is 2:10:40.

[0061] The grade of the talc powder is LJ-110, purchased from Shanghai Liangjiang Chemical Products Co., Ltd.

[0062] The heavy calcium powder is paint-grade heavy calcium powder, purchased from Shanghai Liangjiang Chemical Products Co., Ltd.

[0063] The mesh number of the quartz sand is 100 mesh, the model is snow-white sand, purchased from Changxing Jinlan New Material Technology Co., Ltd.

[0064] The grade of the water reducing agent is Sika 540P, a common commercially available product.

[0065] The cement is P.O 42.5 Conch Cement.

[0066] The particle size of the polystyrene surface non-permeable polymer hollow microspheres is 20μm, purchased from Beijing Zhongke Keyou Technology Co., Ltd.

[0067] The preparation raw materials of the hybrid porous graphene microflowers are specifically 1 part of copper chloride, 12 parts of porous graphene microflowers and 100 parts of alkaline solvent by mass.

[0068] The alkaline solvent is an aqueous potassium hydroxide solution.

[0069] The preparation method of the hybrid porous graphene microflowers is specifically as follows:

[0070] S1. Obtain graphene oxide microflowers by spray drying a monolayer graphene oxide suspension (purchased from Hangzhou Gaoxi Technology Co., Ltd., with a lateral size of 20-30μm) at 140°C. The nozzle used for spray drying is in a two-fluid mode;

[0071] S2. Reduce the graphene oxide microflowers with hydrazine. The mass ratio of hydrazine to graphene oxide microflowers is 1:3. Mix the two and place them in an oven at 80°C for 12 hours. At this time, the mixture changes from yellow to black, and then calcine it in an N 2 environment at a calcination temperature of 1300°C to obtain porous graphene microflowers;

[0072] S3. Disperse cuprous chloride and porous graphene microflowers in an alkaline solvent, control the pH of the system to 9, carry out ultrasonic reaction at 40 °C for 1 h, then filter and collect the product and wash it to obtain a mixture;

[0073] S4. Calcinate the mixture in an N2 environment at a calcination temperature of 420 °C to obtain hybrid porous graphene microflowers.

[0074] The preparation method of the powder material is as follows: uniformly mix a filler, a water reducing agent, polystyrene surface non-permeable polymer hollow microspheres, hybrid porous graphene microflowers and cement to obtain the powder material.

[0075] In the second aspect of this example, a preparation method of a highly water-resistant polymer waterproof coating is provided, specifically: mix the powder material and the liquid material to obtain the highly water-resistant polymer waterproof coating.

[0076] Example 2

[0077] In the first aspect of this example, a highly water-resistant polymer waterproof coating is provided, and its preparation raw materials are a compound of a liquid material and a powder material; among them, the preparation raw materials of the liquid material are, by mass, specifically 85 parts of acrylate emulsion, 0.3 part of wetting agent, 0.2 part of film-forming aid, 0.2 part of defoaming agent and 14.3 parts of water; the preparation raw materials of the powder material are, by mass, specifically 56 parts of filler, 0.4 part of water reducing agent, 3 parts of polystyrene surface non-permeable polymer hollow microspheres, 4 parts of hybrid porous graphene microflowers and 36.6 parts of cement.

[0078] The mass ratio of the liquid material to the powder material is 1:2.

[0079] The brand of the acrylate emulsion is 8316A, purchased from Wanhua Chemical Group.

[0080] The wetting agent is AEO-9, and the model is A9N, purchased from BASF SE.

[0081] The film-forming aid is 1,2-propanediol.

[0082] The defoaming agent is NOPCO NXZ defoaming agent.

[0083] The preparation method of the liquid material includes: uniformly mix acrylate emulsion, wetting agent, film-forming aid, defoaming agent and water to obtain the liquid material.

[0084] The filler is a compound of talc powder, heavy calcium powder and quartz sand.

[0085] The mass ratio of the talc powder, heavy calcium powder and quartz sand is 6:20:30.

[0086] The brand of the talcum powder is LJ-110, purchased from Shanghai Liangjiang Chemical Products Co., Ltd.

[0087] The heavy calcium powder is paint-grade heavy calcium powder, purchased from Shanghai Liangjiang Chemical Products Co., Ltd.

[0088] The mesh number of the quartz sand is 100 mesh, the model is snowflake white sand, purchased from Changxing Jinlan New Material Technology Co., Ltd.

[0089] The brand of the water reducing agent is Sika 540P, a common commercially available product.

[0090] The cement is P.O 42.5 Conch Cement.

[0091] The particle size of the polystyrene surface non-permeable polymer hollow microspheres is 20μm, purchased from Beijing Zhongke Keyou Technology Co., Ltd.

[0092] The preparation raw materials of the hybrid porous graphene microflowers are as follows by mass fraction: specifically, 1 part of copper chloride, 13 parts of porous graphene microflowers and 50 parts of alkaline solvent.

[0093] The alkaline solvent is an aqueous solution of potassium hydroxide.

[0094] The specific preparation method of the hybrid porous graphene microflowers is as follows:

[0095] S1. The monolayer graphene oxide suspension (purchased from Hangzhou Gaoxi Technology Co., Ltd., with a lateral size of 20-30μm) is spray-dried at 140°C to obtain graphene oxide microflowers, and the nozzle used for spray drying is in a two-fluid mode;

[0096] S2. The graphene oxide microflowers are reduced by hydrazine. The mass ratio of hydrazine to graphene oxide microflowers is 1:3. The two are mixed and placed in an oven at 80°C for 12h. At this time, the mixture changes from yellow to black, and then it is calcined in an N 2 environment, and the calcination temperature is 1300°C to obtain porous graphene microflowers;

[0097] S3. Copper chloride and porous graphene microflowers are dispersed in the alkaline solvent, and the pH of the system is controlled to be 9. The mixture is ultrasonically reacted at 30°C for 1.5h, and then the product is filtered and collected and washed to obtain a mixture;

[0098] S4. The mixture is calcined in an N 2 environment, and the calcination temperature is 400°C to obtain the hybrid porous graphene microflowers.

[0099] The preparation method of the powder is as follows: fillers, water reducing agent, polystyrene surface non-permeable polymer hollow microspheres, hybrid porous graphene micro-flowers and cement are uniformly mixed to obtain the powder.

[0100] The second aspect of this example provides a method for preparing a highly water-resistant polymer waterproof coating, specifically, mixing a powder and a liquid to obtain a highly water-resistant polymer waterproof coating.

[0101] Example 3

[0102] The first aspect of this example provides a highly water-resistant polymer waterproof coating, the raw materials for its preparation are a compound of liquid and powder; wherein the raw materials for the preparation of the liquid are, by weight, 90 parts of acrylic emulsion, 0.5 parts of wetting agent, 0.3 parts of film-forming aid, 0.3 parts of defoaming agent and 8.9 parts of water; the raw materials for the preparation of the powder are, by weight, 65 parts of filler, 0.6 parts of water reducer, 4 parts of polystyrene surface non-permeable polymer hollow microspheres, 5 parts of hybrid porous graphene microflowers and 25.4 parts of cement.

[0103] The mass ratio of the liquid material to the powder material is 1:2.5.

[0104] The brand of the acrylic emulsion is 8316A, purchased from Wanhua Chemical Group.

[0105] The wetting agent is AEO-9, model A9N, purchased from BASF AG.

[0106] The film-forming aid is 1,2-propylene glycol.

[0107] The defoamer is NOPCO NXZ defoamer.

[0108] The preparation method of the liquid material comprises: uniformly mixing acrylate emulsion, a wetting agent, a film-forming aid, a defoaming agent and water to obtain the liquid material.

[0109] The filler is a compound of talcum powder, heavy calcium powder and quartz sand.

[0110] The mass ratio of the talcum powder, heavy calcium powder and quartz sand is 10:35:20.

[0111] The talcum powder has a brand name of LJ-110 and is purchased from Shanghai Liangjiang Chemical Products Co., Ltd.

[0112] The heavy calcium powder is coating-grade heavy calcium powder purchased from Shanghai Liangjiang Chemical Products Co., Ltd.

[0113] The mesh number of the quartz sand is 100 meshes, the model is snowflake white sand, and it is purchased from Changxing Jinlan New Material Technology Co., Ltd.

[0114] The brand of the water reducing agent is Sika 540P, a common commercially available product.

[0115] The cement is P.O 42.5 Conch Cement.

[0116] The particle size of the polystyrene surface non-permeable polymer hollow microspheres is 20 μm, purchased from Beijing Zhongke Keyou Technology Co., Ltd.

[0117] The raw materials for preparing the hybrid porous graphene microflowers are as follows by mass fraction: specifically, 1 part of cuprous chloride, 14 parts of porous graphene microflowers, and 33.4 parts of alkaline solvent (i.e., the mass fraction of cuprous chloride in the alkaline solvent is 3 wt%).

[0118] The alkaline solvent is an aqueous solution of potassium hydroxide.

[0119] The preparation method of the hybrid porous graphene microflowers is specifically as follows:

[0120] S1. The monolayer graphene oxide suspension (purchased from Hangzhou Gaoxi Technology Co., Ltd., with a lateral size of 20 - 30 μm) is spray-dried at 140 °C to obtain graphene oxide microflowers. The nozzle used in spray drying is in a two-fluid mode;

[0121] S2. The graphene oxide microflowers are reduced by hydrazine. The mass ratio of hydrazine to graphene oxide microflowers is 1:4. The two are mixed and placed in an oven at 80 °C for 12 h. At this time, the mixture changes from yellow to black, and then it is calcined in an N 2 environment at a calcination temperature of 1300 °C to obtain porous graphene microflowers;

[0122] S3. Cuprous chloride and porous graphene microflowers are dispersed in the alkaline solvent, and the pH of the system is controlled to be 9. Ultrasonic reaction is carried out at 25 °C for 2 h, and then the product is collected by filtration and washed to obtain a mixture;

[0123] S4. The mixture is calcined in an N 2 environment at a calcination temperature of 410 °C to obtain the hybrid porous graphene microflowers.

[0124] The preparation method of the powder material is as follows: The filler, water reducing agent, polystyrene surface non-permeable polymer hollow microspheres, hybrid porous graphene microflowers, and cement are mixed evenly to obtain the powder material.

[0125] In the second aspect of this example, a preparation method of a highly water-resistant polymer waterproof coating is provided, specifically as follows: The powder material and the liquid material are mixed to obtain the highly water-resistant polymer waterproof coating.

[0126] Comparative Example 1 (without adding polystyrene surface non-permeable polymer hollow microspheres)

[0127] The first aspect of this example provides a highly water-resistant polymer waterproof coating, the raw materials for its preparation are a compound of liquid and powder; wherein the raw materials for the preparation of the liquid are, in terms of weight percentage, 85 parts of acrylic emulsion, 0.3 parts of wetting agent, 0.2 parts of film-forming aid, 0.2 parts of defoaming agent and 14.3 parts of water; the raw materials for the preparation of the powder are, in terms of weight percentage, 56 parts of filler, 0.4 parts of water reducer, 4 parts of hybrid porous graphene microflowers and 39.6 parts of cement.

[0128] The mass ratio of the liquid material to the powder material is 1:2.

[0129] The brand of the acrylic emulsion is 8316A, purchased from Wanhua Chemical Group.

[0130] The wetting agent is AEO-9, model A9N, purchased from BASF AG.

[0131] The film-forming aid is 1,2-propylene glycol.

[0132] The defoamer is NOPCO NXZ defoamer.

[0133] The preparation method of the liquid material comprises: uniformly mixing acrylate emulsion, a wetting agent, a film-forming aid, a defoaming agent and water to obtain the liquid material.

[0134] The filler is a compound of talcum powder, heavy calcium powder and quartz sand.

[0135] The mass ratio of the talcum powder, heavy calcium powder and quartz sand is 6:20:30.

[0136] The talcum powder has a brand name of LJ-110 and is purchased from Shanghai Liangjiang Chemical Products Co., Ltd.

[0137] The heavy calcium powder is coating-grade heavy calcium powder purchased from Shanghai Liangjiang Chemical Products Co., Ltd.

[0138] The mesh number of the quartz sand is 100 meshes, the model is snowflake white sand, and it is purchased from Changxing Jinlan New Material Technology Co., Ltd.

[0139] The brand of the water reducing agent is Sika 540P, which is a common commercial product.

[0140] The cement is PO 42.5 Conch cement.

[0141] The raw materials for preparing the hybrid porous graphene micro-flowers are specifically 1 part of cuprous chloride, 13 parts of porous graphene micro-flowers and 50 parts of alkaline solvent, calculated by weight.

[0142] The alkaline solvent is an aqueous potassium hydroxide solution.

[0143] The preparation method of the hybrid porous graphene microflowers is specifically as follows:

[0144] S1. Obtain graphene oxide microflowers by spray-drying a monolayer graphene oxide suspension (purchased from Hangzhou Graphene Technology Co., Ltd., with a lateral size of 20 - 30 μm) at 140 °C. The nozzle used for spray-drying is in a two-fluid mode;

[0145] S2. Reduce the graphene oxide microflowers with hydrazine. The mass ratio of hydrazine to graphene oxide microflowers is 1:3. Mix the two and place them in an oven at 80 °C for reaction for 12 h. At this time, the mixture changes from yellow to black, and then calcine it in an N 2 environment at a calcination temperature of 1300 °C to obtain porous graphene microflowers;

[0146] S3. Disperse cuprous chloride and the porous graphene microflowers in an alkaline solvent, control the pH of the system to 9, carry out ultrasonic reaction at 35 °C for 1.5 h, then filter and collect the product and wash it to obtain a mixture;

[0147] S4. Calcine the mixture in an N 2 environment at a calcination temperature of 400 °C to obtain the hybrid porous graphene microflowers.

[0148] The preparation method of the powder material is: Mix the filler, water reducer, hybrid porous graphene microflowers and cement evenly to obtain the powder material.

[0149] In the second aspect of this example, a preparation method of a highly water-resistant polymer waterproof coating is provided, specifically: Mix the powder material and the liquid material to obtain the highly water-resistant polymer waterproof coating.

[0150] Comparative Example 2 (without adding hybrid porous graphene microflowers)

[0151] In the first aspect of this example, a highly water-resistant polymer waterproof coating is provided, and its preparation raw materials are a compound of a liquid material and a powder material; among them, the preparation raw materials of the liquid material are, by mass, specifically 85 parts of acrylate emulsion, 0.3 part of wetting agent, 0.2 part of film-forming aid, 0.2 part of defoaming agent and 14.3 parts of water; the preparation raw materials of the powder material are, by mass, specifically 56 parts of filler, 0.4 part of water reducer, 3 parts of polystyrene surface non-permeable polymer hollow microspheres and 40.6 parts of cement.

[0152] The mass ratio of the liquid material to the powder material is 1:1.5.

[0153] The acrylate emulsion has the brand number 8316A and is purchased from Wanhua Chemical Group.

[0154] The wetting agent is AEO-9, with the model number A9N, purchased from BASF SE.

[0155] The film-forming auxiliary is 1,2-propanediol.

[0156] The defoamer is NOPCO NXZ defoamer.

[0157] The preparation method of the liquid material includes: mixing the acrylate emulsion, wetting agent, film-forming auxiliary, defoamer and water evenly to obtain the liquid material.

[0158] The filler is a compound of talc powder, heavy calcium powder and quartz sand.

[0159] The mass ratio of the talc powder, heavy calcium powder and quartz sand is 2:10:40.

[0160] The grade of the talc powder is LJ-110, purchased from Shanghai Liangjiang Chemical Products Co., Ltd.

[0161] The heavy calcium powder is coating-grade heavy calcium powder, purchased from Shanghai Liangjiang Chemical Products Co., Ltd.

[0162] The mesh number of the quartz sand is 100 mesh, the model is snow-white sand, purchased from Changxing Jinlan New Material Technology Co., Ltd.

[0163] The grade of the water reducer is Sika 540P, a common commercially available product.

[0164] The cement is P.O 42.5 Conch Cement.

[0165] The particle size of the polystyrene surface non-permeable polymer hollow microspheres is 20μm, purchased from Beijing Zhongke Keyou Technology Co., Ltd.

[0166] The preparation method of the powder material is: mixing the filler, water reducer, polystyrene surface non-permeable polymer hollow microspheres and cement evenly to obtain the powder material.

[0167] In the second aspect of this example, a preparation method of a high water-resistant polymer waterproof coating is provided, specifically: mixing the powder material and the liquid material to obtain the high water-resistant polymer waterproof coating.

[0168] Comparative Example 3 (less addition amount of hybrid porous graphene microflowers)

[0169] The first aspect of this example provides a highly water-resistant polymer waterproof coating, the raw materials for its preparation include liquid and powder; wherein the raw materials for the preparation of the liquid are, by weight, 85 parts of acrylic emulsion, 0.3 parts of wetting agent, 0.2 parts of film-forming aid, 0.2 parts of defoaming agent and 14.3 parts of water; the raw materials for the preparation of the powder are, by weight, 56 parts of filler, 0.4 parts of water reducer, 3 parts of polystyrene surface non-permeable polymer hollow microspheres, 1 part of hybrid porous graphene microflowers and 39.6 parts of cement.

[0170] The mass ratio of the liquid material to the powder material is 1:2.

[0171] The brand of the acrylic emulsion is 8316A, purchased from Wanhua Chemical Group.

[0172] The wetting agent is AEO-9, model A9N, purchased from BASF AG.

[0173] The film-forming aid is 1,2-propylene glycol.

[0174] The defoamer is NOPCO NXZ defoamer.

[0175] The preparation method of the liquid material comprises: uniformly mixing acrylate emulsion, a wetting agent, a film-forming aid, a defoaming agent and water to obtain the liquid material.

[0176] The filler is a compound of talcum powder, heavy calcium powder and quartz sand.

[0177] The mass ratio of the talcum powder, heavy calcium powder and quartz sand is 6:20:30.

[0178] The talcum powder has a brand name of LJ-110 and is purchased from Shanghai Liangjiang Chemical Products Co., Ltd.

[0179] The heavy calcium powder is coating-grade heavy calcium powder purchased from Shanghai Liangjiang Chemical Products Co., Ltd.

[0180] The mesh number of the quartz sand is 100 meshes, the model is snowflake white sand, and it is purchased from Changxing Jinlan New Material Technology Co., Ltd.

[0181] The brand of the water reducing agent is Sika 540P, which is a common commercial product.

[0182] The cement is PO 42.5 Conch cement.

[0183] The particle size of the polystyrene surface impermeable polymer hollow microspheres is 20 μm and is purchased from Beijing Zhongke Keyou Technology Co., Ltd.

[0184] The preparation raw materials of the hybrid porous graphene microflowers are as follows by mass fraction: 1 part of cuprous chloride, 13 parts of porous graphene microflowers and 50 parts of alkaline solvent.

[0185] The alkaline solvent is an aqueous solution of potassium hydroxide.

[0186] The preparation method of the hybrid porous graphene microflowers is as follows:

[0187] S1. Obtain graphene oxide microflowers by spray drying a monolayer graphene oxide suspension (purchased from Hangzhou Graphene Technology Co., Ltd., with a lateral size of 20 - 30 μm) at 140 °C. The nozzle used for spray drying is in a two-fluid mode;

[0188] S2. Reduce the graphene oxide microflowers with hydrazine. The mass ratio of hydrazine to graphene oxide microflowers is 1:3. Mix the two and place them in an oven at 80 °C for reaction for 12 h. At this time, the mixture changes from yellow to black, and then calcine it in an N 2 environment at a calcination temperature of 1300 °C to obtain porous graphene microflowers;

[0189] S3. Disperse cuprous chloride and porous graphene microflowers in the alkaline solvent, control the pH of the system to 9, carry out ultrasonic reaction at 40 °C for 1.5 h, then filter and collect the product and wash it to obtain a mixture;

[0190] S4. Calcine the mixture in an N 2 environment at a calcination temperature of 410 °C to obtain the hybrid porous graphene microflowers.

[0191] The preparation method of the powder material is as follows: Mix the filler, water reducer, polystyrene surface non-permeable polymer hollow microspheres, hybrid porous graphene microflowers and cement evenly to obtain the powder material.

[0192] In the second aspect of this example, a preparation method of a highly water-resistant polymer waterproof coating is provided, specifically: Mix the powder material and the liquid material to obtain the highly water-resistant polymer waterproof coating.

[0193] Comparative Example 4 (relatively large addition amount of hybrid porous graphene microflowers)

[0194] In the first aspect of this example, a highly water-resistant polymer waterproof coating is provided, and its preparation raw materials are a compound of a liquid material and a powder material; among them, the preparation raw materials of the liquid material are as follows by mass fraction: 85 parts of acrylate emulsion, 0.3 part of wetting agent, 0.2 part of film-forming aid, 0.2 part of defoaming agent and 14.3 parts of water; the preparation raw materials of the powder material are as follows by mass fraction: 56 parts of filler, 0.4 part of water reducer, 3 parts of polystyrene surface non-permeable polymer hollow microspheres, 6 parts of hybrid porous graphene microflowers and 34.6 parts of cement.

[0195] The mass ratio of the liquid material to the powder material is 1:2.

[0196] The grade of the acrylate emulsion is 8316A, purchased from Wanhua Chemical Group.

[0197] The wetting agent is AEO-9, and the model is A9N, purchased from BASF SE.

[0198] The film-forming auxiliary agent is 1,2-propanediol.

[0199] The defoaming agent is NOPCO NXZ defoaming agent.

[0200] The preparation method of the liquid material is: mixing the acrylate emulsion, wetting agent, film-forming auxiliary agent, defoaming agent and water evenly to obtain the liquid material.

[0201] The filler is a compound of talc powder, heavy calcium powder and quartz sand.

[0202] The mass ratio of the talc powder, heavy calcium powder and quartz sand is 6:20:30.

[0203] The grade of the talc powder is LJ-110, purchased from Shanghai Liangjiang Chemical Products Co., Ltd.

[0204] The heavy calcium powder is paint-grade heavy calcium powder, purchased from Shanghai Liangjiang Chemical Products Co., Ltd.

[0205] The mesh number of the quartz sand is 100 mesh, the model is snow-white sand, purchased from Changxing Jinlan New Materials Technology Co., Ltd.

[0206] The grade of the water reducing agent is Sika 540P, a commonly available product on the market.

[0207] The cement is P.O 42.5 Conch Cement.

[0208] The particle size of the polystyrene surface non-permeable polymer hollow microspheres is 20 μm, purchased from Beijing Zhongke Keyou Technology Co., Ltd.

[0209] The raw materials for the preparation of the hybrid porous graphene microflowers are, by mass, specifically 1 part of cuprous chloride, 13 parts of porous graphene microflowers and 50 parts of alkaline solvent.

[0210] The alkaline solvent is an aqueous potassium hydroxide solution.

[0211] The specific preparation method of the hybrid porous graphene microflowers is:

[0212] S1. Obtain graphene oxide microflowers by spray-drying a single-layer graphene oxide suspension (purchased from Hangzhou Gaoxi Technology Co., Ltd., with a lateral size of 20 - 30 μm) at 140 °C. The nozzle used in spray-drying is in a two-fluid mode;

[0213] S2. Reduce the graphene oxide microflowers using hydrazine, where the mass ratio of hydrazine to graphene oxide microflowers is 1:3. Mix the two and place them in an oven at 80 °C for 12 h. At this time, the mixture changes from yellow to black, and then calcine it in an N 2 environment at a calcination temperature of 1300 °C to obtain porous graphene microflowers;

[0214] S3. Disperse cuprous chloride and porous graphene microflowers in an alkaline solvent, control the pH of the system to 9, and ultrasonically react at 30 °C for 1.5 h. Then filter and collect the product and wash it to obtain a mixture;

[0215] S4. Calcine the mixture in an N 2 environment at a calcination temperature of 400 °C to obtain hybrid porous graphene microflowers.

[0216] The preparation method of the powder material is as follows: Mix the filler, water reducer, polystyrene surface non-permeable polymer hollow microspheres, hybrid porous graphene microflowers and cement evenly to obtain the powder material.

[0217] In the second aspect of this example, a preparation method of a highly water-resistant polymer waterproof coating is provided. Specifically: Mix the powder material and the liquid material to obtain the highly water-resistant polymer waterproof coating.

[0218] Comparative Example 5 (The preparation of hybrid porous graphene microflowers does not go through calcination)

[0219] In the first aspect of this example, a highly water-resistant polymer waterproof coating is provided, and its preparation raw materials are a compound of a liquid material and a powder material; among them, the preparation raw materials of the liquid material are, by mass, specifically 85 parts of acrylate emulsion, 0.3 part of wetting agent, 0.2 part of film-forming aid, 0.2 part of defoaming agent and 14.3 parts of water; the preparation raw materials of the powder material are, by mass, specifically 56 parts of filler, 0.4 part of water reducer, 3 parts of polystyrene surface non-permeable polymer hollow microspheres, 4 parts of hybrid porous graphene microflowers and 36.6 parts of cement.

[0220] The mass ratio of the liquid material to the powder material is 1:2.

[0221] The grade of the acrylate emulsion is 8316A, purchased from Wanhua Chemical Group.

[0222] The wetting agent is AEO-9, and the model is A9N, purchased from BASF SE.

[0223] The film-forming auxiliary agent is 1,2-propanediol.

[0224] The defoaming agent is NOPCO NXZ defoaming agent.

[0225] The preparation method of the liquid material includes: mixing acrylate emulsion, wetting agent, film-forming auxiliary agent, defoaming agent and water evenly to obtain the liquid material.

[0226] The filler is a compound of talc powder, heavy calcium powder and quartz sand.

[0227] The mass ratio of the talc powder, heavy calcium powder and quartz sand is 6:20:30.

[0228] The grade of the talc powder is LJ-110, purchased from Shanghai Liangjiang Chemical Products Co., Ltd.

[0229] The heavy calcium powder is paint-grade heavy calcium powder, purchased from Shanghai Liangjiang Chemical Products Co., Ltd.

[0230] The mesh number of the quartz sand is 100 mesh, the model is snowflake white sand, purchased from Changxing Jinlan New Material Technology Co., Ltd.

[0231] The grade of the water reducing agent is Sika 540P, a common commercially available product.

[0232] The cement is P.O 42.5 Conch Cement.

[0233] The particle size of the polystyrene surface non-permeable polymer hollow microspheres is 20μm, purchased from Beijing Zhongke Keyou Technology Co., Ltd.

[0234] The preparation raw materials of the hybrid porous graphene microflowers are specifically 1 part of copper chloride and 9 parts of porous graphene microflowers by mass.

[0235] The preparation method of the hybrid porous graphene microflowers is specifically as follows:

[0236] S1. Spray-dry the single-layer graphene oxide suspension (purchased from Hangzhou Gaoxi Technology Co., Ltd., with a lateral size of 20 - 30μm) at 140°C to obtain graphene oxide microflowers. The nozzle used for spray drying is in a two-fluid mode;

[0237] S2. Reduce the graphene oxide microflowers with hydrazine. The mass ratio of hydrazine to graphene oxide microflowers is 1:3. Mix the two and place them in an oven at 80°C for reaction for 12h. At this time, the mixture changes from yellow to black, and then calcine it in an N 2 environment at a calcination temperature of 1300°C to obtain porous graphene microflowers;

[0238] S3. Mix cuprous chloride and porous graphene microflowers evenly to obtain hybrid porous graphene microflowers.

[0239] The preparation method of the powder material is as follows: Mix the filler, water reducer, polystyrene surface non-permeable polymer hollow microspheres, hybrid porous graphene microflowers and cement evenly to obtain the powder material.

[0240] In the second aspect of this example, a preparation method of a highly water-resistant polymer waterproof coating is provided, specifically: Mix the powder material and the liquid material to obtain the highly water-resistant polymer waterproof coating.

[0241] Performance Test

[0242] Test objects: The highly water-resistant polymer waterproof coatings prepared in Examples 1-3 and Comparative Examples 1-5, and the waterproof coatings prepared by brushing the coatings.

[0243] Test items and methods:

[0244] 1. Initial density after coating mixing: Test according to the standard of "GB / T 6750-2007 Determination of the density of paints and varnishes".

[0245] 2. Pencil hardness of the coating film: Test according to the standard of "GB / T 6739-2022 Determination of film hardness by pencil method for paints and varnishes", where the thickness of the coating film is (1.5 ± 0.2) mm.

[0246] 3. Water absorption rate of the coating film: Test according to the content of Part 6.15 in "GB / T 19250-2013 Polyurethane waterproof coating", where the thickness of the coating film is (1.5 ± 0.2) mm.

[0247] 4. Tensile strength of the coating film: Test according to the standard of "GB / T 23445-2009 Polymer cement waterproof coating", where the thickness of the coating film is (1.5 ± 0.2) mm.

[0248] The experimental results of the above test items 1-4 are shown in Table 1.

[0249] Table 1

[0250]

[0251] It can be seen from the experimental results in Table 1 that the coatings of the waterproof coatings prepared in Examples 1-3 of the present invention have relatively high hardness, the water absorption rate is lower than 5%, the tensile strength is not lower than 2.0 MPa, the elongation at break is not lower than 90%, and the highest can reach more than 270%.

[0252] In Comparative Example 1, due to the lack of polystyrene surface non-permeable polymer hollow microspheres in the preparation raw materials, the initial density of the waterproof coating is relatively large, which is not conducive to coating.

[0253] In Comparative Example 2, due to the lack of hybrid porous graphene microflowers in the preparation raw materials, the water absorption rate of the waterproof coating film increased significantly, which was not conducive to normal use.

[0254] In Comparative Examples 3-4, since the usage amount of the hybrid porous graphene microflowers did not meet the optimal limit, the water absorption performance and mechanical properties of the waterproof coating would be affected to a certain extent.

[0255] In Comparative Example 5, since the preparation process of the hybrid porous graphene microflowers only involved the mixing of raw materials cuprous chloride and porous graphene microflowers without further calcination treatment, the water absorption performance and elongation at break of the waterproof coating would also be affected to a certain extent.

Claims

1. A highly water-resistant polymer waterproof coating, characterized in that: The preparation raw materials include liquid materials and powder materials; The raw materials for preparing the liquid material include, by weight, 80-90 parts of acrylic emulsion, 0.1-0.5 parts of wetting agent, 0.1-0.3 parts of film-forming aid, 0.1-0.3 parts of defoaming agent and 5-30 parts of water; The raw materials for preparing the powder include, by weight, 32-85 parts of filler, 0.1-0.6 parts of water reducing agent, 2-4 parts of polystyrene surface non-permeable polymer hollow microspheres, 3-5 parts of hybrid porous graphene micro-flowers, and 20-50 parts of cement.

2. The highly water-resistant polymer waterproof coating according to claim 1, characterized in that: The acrylic ester emulsion includes anionic acrylic ester emulsion.

3. The highly water-resistant polymer waterproof coating according to claim 1, characterized in that: The filler includes talcum powder, heavy calcium powder and quartz sand.

4. The highly water-resistant polymer waterproof coating according to claim 3, characterized in that: The mass ratio of the talcum powder, heavy calcium powder and quartz sand is (2-10): (10-35): (20-40).

5. The highly water-resistant polymer waterproof coating according to claim 1, characterized in that: The particle size of the polystyrene surface impermeable polymer hollow microspheres is 10-30 μm.

6. The highly water-resistant polymer waterproof coating according to claim 1, characterized in that: The raw materials for preparing the hybrid porous graphene micro-flowers include cuprous chloride, porous graphene micro-flowers and alkaline solvent.

7. The highly water-resistant polymer waterproof coating according to claim 6, characterized in that: The mass ratio of the cuprous chloride to the porous graphene micro-flowers is 1:(12-14).

8. The highly water-resistant polymer waterproof coating according to claim 6, characterized in that: The preparation method of the hybrid porous graphene micro-flower comprises: S1. Dispersing cuprous chloride and porous graphene microflowers in an alkaline solvent, subjecting the mixture to ultrasonic reaction at 25-40° C. for 1-3 h, and then collecting the product by filtration and washing to obtain a mixture; S2. The mixture is calcined in a N2 environment at a calcination temperature of 400-420° C. to obtain hybrid porous graphene microflowers.

9. The highly water-resistant polymer waterproof coating according to any one of claims 1 to 8, characterized in that: The mass ratio of the liquid material to the powder material is 1:1.5-2.

5.

10. A method for preparing a highly water-resistant polymer waterproof coating according to any one of claims 1 to 9, characterized in that: include: The powder and liquid are mixed to obtain a highly water-resistant polymer waterproof coating.

Citation Information

Patent Citations

  • A method for preparing a graphene oxide-reinforced waterproof polymer emulsion

    CN110591009B

  • Cement-based polymer waterproof coating

    CN114854260A

  • High-water-resistance polymer cement waterproof coating and preparation method thereof

    CN115011156A